Artificial Intelligence in Business: Transforming Operations, Decision Making, and Strategic - Soneji, Harsh Metgud (Journal of Global Economy, Business and Finance, 2026)
The rise of Artificial Intelligence (AI) is redefining business operations worldwide, bringing automation, efficiency, and advanced decision - making to various industries. AI technologies such as machine learning, natural language processing, and robotics are replacing repetitive tasks, enabling data - driven insights, and enhancing customer experiences. Businesses are leveraging AI for supply chain optimization, predictive analytics, and talent management, driving competitive advantage in a rapidly evolving market. However, this transformation is not without challenges—concerns around workforce displacement, data privacy, and algorithmic bias highlight the ethical considerations of AI adoption. In my view, the key to sustainable AI integration lies in balancing technological advancements with responsible governance, ensuring that businesses harness AI’s potential while addressing its risks. As AI continues to evolve, organizations must adapt proactively, fostering a culture of innovation and ethical AI use to remain ahead in the digital era.